PENGARUH RASIO MOL, SUHU DAN LAMA REAKSI TERHADAP TEGANGAN PERMUKAAN DAN STABILITAS EMULSI METIL ESTER SULFONAT DARI CPO - Hidayati, Sri (Jurnal Teknologi & Industri Hasil Pertanian, 2012)
A surfactant is a surface-active agent that can be produced by chemical or biochemical synthesis. The main characteristic of a surfactant is having polar and non polar groups at the same molecule (amphiphilic molecules) and forming head-tail configuration. This research is aimed to obtain the optimum conditions (reaction temperature, sulphonation reaction and molar ratio) of sulphonation process in producing MES from CPO methyl ester and to investigate the characteristic of MES produced. Measurements conducted include surface tension and emulsion stability. Experimental design used was Response Surface Method (RSM) and Central Composite Design (CCD) with three factors. Result showed that MES characteristic include surface tension of 33-34,9 dyne/cm and ability to increase emulsion stability of 55-80,3%. It was also shown that the best condition of sulphonation process was obtained with the ratio of reactant of 1:1,5, reaction time of 4,5 hour and reaction temperature of 106oC. MES resulted from best condition had following characteristics of surface tension of 33 dyne/cm and ability to increase emulsion stability of 70%. Keywords: metil ester sulfonat, surface tension, emulsion stability